Purchase intention produk ramah lingkungan: Pendekatan theory of planned behavior - Octavia, Cecilia Dwi; Handayani, Wahyu Prabawati Putri (Journal of Management and Digital Business, 2025)
This study analyzes the influence of attitude, subjective norm, and perceived behavioral control on purchase intention for environmentally friendly products. The sample consisted of 100 active students from Widya Mandala Catholic University Surabaya, Madiun Campus, collected using Google Forms with purposive sampling. Data analysis was conducted using multiple linear regression. The results indicate that attitude, subjective norm, and perceived behavioral control significantly influence the purchase intention of environmentally friendly products. Positive attitude, social support from the environment, and high self-control contribute to increasing consumers' purchase intention. These findings confirm that the stronger these three factors are, the higher consumers' intention to purchase environmentally friendly products, consistent with the Theory of Planned Behavior framework.